2015
DOI: 10.1080/08952841.2014.950141
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Meaning of Identity in Retired Professional Women

Abstract: Through this study we sought to understand the complex experience of retirement and the meaning of identity for women who recently retired from a professional career. Through the use of qualitative methods, including photo elicitation, journaling, and a series of two in-depth interviews with each of six women, a fluid description of the meaning of identity among a small, homogenous sample of retired professional women was constructed. Salient themes included consistency of significant identity components from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…American women and noted similar results to Price (2003). In particular Borrero and Kruger (2015) found that role continuity (outside of work) was important for the women to maintain a constant self-identity. In addition, their in-depth qualitative interviews provided further support for researchers to acknowledge that there appear to be clear differences between the retirement experiences of men and women.…”
Section: A18 Qualitative Retirement Researchmentioning
confidence: 52%
See 2 more Smart Citations
“…American women and noted similar results to Price (2003). In particular Borrero and Kruger (2015) found that role continuity (outside of work) was important for the women to maintain a constant self-identity. In addition, their in-depth qualitative interviews provided further support for researchers to acknowledge that there appear to be clear differences between the retirement experiences of men and women.…”
Section: A18 Qualitative Retirement Researchmentioning
confidence: 52%
“…Price (2003) also acknowledged that up until this point, research had failed to take into account the complexity involved in a woman's retirement journey, which meant that their experiences were being overlooked. Borrero and Kruger (2015) conducted phenomenological research on six retired…”
Section: A18 Qualitative Retirement Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging in "identity talk" (see Snow & Anderson, 1987), they attempted to retain the status associated with their social identities as professionals. Other studies support the finding that professional women experience considerable identity consistency from work to retirement (Borrero & Kruger, 2015;Price, 2002). Women often substitute the loss of their professional roles with alternative roles that are extensions of their former professional lives (Price, 2003).…”
Section: Identity Perspectivesmentioning
confidence: 83%
“…Theories of identity development argue that individuals form a sense of self through engaging in a series of roles and internalising the social meanings attached to them. This continues throughout the life course (Borrero & Kruger, 2015;Stryker & Burke, 2000). Early studies of retirement drawing on role theory, focusing on the loss of the work role as a key life transition (Price, 2003;Slevin & Wingrove, 1995), were precursors to identity perspectives on retirement.…”
Section: Identity Perspectivesmentioning
confidence: 99%